Intelligent Decision Technologies 2016 Proceedings of the 8th KES International Conference on Intelligent Decision Technologies (KES-IDT 2016) - Part II - Czarnowski, Ireneusz; Caballero, Alfonso Mateos; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The KES-IDT-2016 proceedings give an excellent insight into recent research, both theoretical and applied, in the field of intelligent decision making. The range of topics explored is wide, and covers methods of grouping, classification, prediction, decision support, modelling and many more in such areas as finance, linguistics, medicine, management and transportation. This proceedings contain several sections devoted to specific topics, such as: · Specialized Decision Techniques for Data Mining, Transportation and Project Management · Pattern Recognition for Decision Making Systems · New Advances of Soft Computing in Industrial and Management Engineering · Recent Advances in Fuzzy Systems · Intelligent Data Analysis and Applications · Reasoning-based Intelligent Systems · Intelligent Methods for Eye Movement Data Processing and Analysis · Intelligent Decision Technologies for Water Resources Management · Intelligent Decision Making for Uncertain Unstructured Big Data · Decision Making Theory for Economics · Interdisciplinary Approaches in Business Intelligence Research and Practice · Pattern Recognition in Audio and Speech Processing The KES-IDT conference is a well-established international annual conference, interdisciplinary in nature. These two volumes of proceedings form an excellent account of the latest results and outcomes of recent research in this leading-edge area. .
Intelligent Data Analysis and Applications -- Intelligent Decision Making for Uncertain Unstructured Big Data -- Reasoning-based Intelligent Systems -- Recent Advances in Fuzzy Systems -- Intelligent Methods for Eye Movement Data Processing and Analysis -- Intelligent Decision Technologies for Water Resources Management -- Decision Making Theory for Economics -- Interdisciplinary Approaches in Business Intelligence Research and Practice.-Pattern Recognition in Audio and Speech Processing.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence